Multiple environmental cues impact habitat choice during nocturnal homing of specialized reef shrimp. (15th December 2018) - Ashur, Molly M; Dixson, Danielle L
Abstract: Habitat selection is a critical process for animals throughout their life, and adult organisms that travel to forage or mate must reselect habitat frequently. On coral reefs, competition for space has led to a high proportion of habitat specialists. Habitat selection is especially vital for organisms that require specialized habitat; however, research has primarily focused on the initial habitat choice made during the larval/juvenile stage. Here, we analyze habitat selection in the adult sponge-dwelling reef shrimp, Lysmata pederseni . Using a mark-and-recapture technique, belt transects, patch reefs, and cue isolation experiments, this study reveals that adult L. pederseni diurnally reselect habitat and a natural preference exists for specific sponge species and shapes. This natural preference is a function of chemical and morphological cues as well as sponge distribution. As habitat specialists can drive biodiversity, understanding the mechanisms behind habitat selection can inform research and management practices. Abstract : Is architecture more important than smell when choosing a home? Here, we investigate the external cues involved in habitat selection of a sponge-associated shrimp after nightly forays on the reef. By tracking shrimp locations through time and isolating environmental variables, we conclude that while both sponge shape and chemical cues play a role in habitat selection, shape may be a more critical factor for resident shrimp.